Nasal Continuous Positive Airway Pressure vs. Nasal Intermittent Positive Pressure Ventilation as Initial Treatment After Birth in Extremely Preterm Infants - Yasemin Ezgi Kostekci; Emel Okulu; Batuhan Bakirarar; Elvis Kraja; Omer Erdeve; Begum Atasay; Saadet Arsan (Frontiers Media S.A., 2022)
ObjectiveNon-invasive respiratory support strategies are known to reduce the complications of invasive mechanical ventilation in preterm infants. Nasal continuous positive airway pressure (NCPAP) and nasal intermittent positive pressure ventilation (NIPPV) are commonly used ones. The recent meta-analyses indicated that early NIPPV did appear to be superior to NCPAP for decreasing respiratory failure and the need for intubation among preterm infants with respiratory distress syndrome (RDS). The aim of the study was to compare the short-term outcomes of extremely preterm infants who received NCPAP or NIPPV as an initial treatment of RDS.MethodsThis retrospective study included infants born before 29 weeks' gestation between 1 January 2018 and 31 December 2021 who received non-invasive respiratory support with NCPAP or NIPPV. For every infant included in the cohort, only the first episode of NCPAP or NIPPV as initial treatment was evaluated. The primary outcome was the need for intubation within 72 h, and the secondary outcomes were the need for intubation within 7 days, administration of surfactant, prematurity-related morbidities, mortality, and death or bronchopulmonary dysplasia (BPD).ResultsDuring the study period, there were 116 inborn admissions of preterm infants born <29 weeks' gestation and 60 of them met the inclusion criteria. Of these, 31 (52%) infants received NCPAP while 29 (48%) infants received NIPPV at the first hours after birth. There were no differences in the baseline demographics between the groups (p > 0.05). Blood gas parameters (pH, pCO2, HCO3, and lactate) at admission were not different. The need for intubation within 72 h as the primary outcome was similar between NCPAP and NIPPV groups (35.5 vs. 34.5%, p = 0.935). The rates of surfactant requirement, need for intubation within 7 days, prematurity-related morbidities, mortality, and death/BPD were similar among the groups (p > 0.05).ConclusionNasal intermittent positive pressure ventilation is non-inferior to NCPAP as an initial treatment in extremely preterm infants with RDS. Although the rate of intubation in the first week, mortality, and BPD did not differ between groups, additional studies are needed and the synchronization of NIPPV should be evaluated.